(untitled) (Journal Of Educational and Psychological Researches, 2016)
The research endeavored to single out the problems, difficulties and obstacles faced by the members of the staff of Baghdad University. The importance of research, then, depends upon the importance of the university lecturers and their vital role in developing the society. The goals of the research are summarized in knowing the main problems facing those university lectures and relative weight of these problems in addition to identifying the differences in their opinions to these problems according to the specializations variables (scientific, humanistic), the gender (males, females) and the Scientific grade (professor, assistant professor, lecturer, assistant lecturer. The research is limited to a specimen of lecturers from the university numbered (192) of the academic year 2013 -2014. The related terms of the research were identified and the theoretical literatures connected with our topic were displayed in addition to a group of previous local and Arabic studies. Many procedures were taken represented by choosing a simple random specimen. Accordingly, a special device was suggested through the previous studies in addition to open question. The final items of the questionnaire are (36) distributed upon (9) dimensions, while the results of the virtual truth of device showed that the increasing of the problems is connecting with the turbulent security and political status in addition to other detailed results. In order to improve this image, the researcher suggested a number of recommendations and suggestions.